Booms, Busts, and Fraud - Povel, Paul; Singh, Rajdeep; Winton, Andrew (Review of Financial Studies, 2007)
Firms sometimes commit fraud by altering publicly reported information to be more favorable, and investors can monitor firms to obtain more accurate information. We study equilibrium fraud and monitoring decisions. Fraud is most likely to occur in relatively good times, and the link between fraud and good times becomes stronger as monitoring costs decrease. Nevertheless, improving business conditions may sometimes diminish fraud. We provide an explanation for why fraud peaks towards the end of a boom and is then revealed in the ensuing bust. We also show that fraud can increase if firms make more information available to the public. (JEL E320, G300, G380) Booms and busts are a common feature of market economies. Almost as common is the belief that a boom encourages and conceals financial fraud and misrepresentation by firms, which are then revealed by the ensuing bust. Examples in the last century include the 1920s [Galbraith (1955)], the ‘‘go-go’ ’ market of the 1960s and early 1970s [Labaton (2002), Schilit (2002)], and the use of junk bonds and LBOs in the 1980s [Kaplan and